When coworking space and setting boundaries affect well-being of remote workers - Khoury, Samar (Technium Social Sciences Journal, 2025)
Background: Establishing clear boundaries would help remote workers delineate their professional responsibilities from their personal time and promoting a healthier work-life balance. this study aims to investigate the impact of different living arrangements and boundary-setting strategies on overall well-being. Methods: In a cross-sectional design, a total of 293 workers participated in an online survey. Well-being was measured using the 14-item Scale of General Well-Being (14-SGWB). Results: Only 35.8% of remote workers had a dedicated desk at home in a room with a door that can be closed. Around 35% stated that the boundaries set between work and personal life were a little unclear and 38.5% reported often feeling that work intruded on their personal time. Linear regression analysis showed that setting clearer work-life boundaries (Beta=2.46), having comfort in people around them (Beta=4.46) were significantly associated with higher well-being scores. Conclusion: a dedicated workstations, clear boundaries, and support from cohabitants positively impact remote workers well-being. It is recommended that organizations prioritize the implementation of supportive measures such as training programs, flexible work arrangements, and clear communication channels to enhance the well-being of their remote workforce.